1966
DOI: 10.3758/bf03331029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of overtraining and two non-correction training procedures upon a brightness discrimination reversal

Abstract: Effects of overtraining and two non-correction training procedures upon a brightness discrimination reversal JThe effects of overlearning and two non-correction training procedures upon the reversal of a black-white discrimination task were investigated. Overtraining and the Non-Entry procedure facilitated reversal learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1969
1969
1972
1972

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In those cases where data are available, all successful demonstrations of the ORE have in fact used a relatively large reward. This includes, in addition to experiments mentioned in earlier reviews (see Mackintosh, 1965a), such recent studies as Maiidler (1968), Paul (1966), andSiegel (1967). The smallest reward specified in a successful experiment is 5-sec.…”
Section: Reward Size and Frustrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In those cases where data are available, all successful demonstrations of the ORE have in fact used a relatively large reward. This includes, in addition to experiments mentioned in earlier reviews (see Mackintosh, 1965a), such recent studies as Maiidler (1968), Paul (1966), andSiegel (1967). The smallest reward specified in a successful experiment is 5-sec.…”
Section: Reward Size and Frustrationmentioning
confidence: 99%
“…The earlier evidence was reviewed by Mackintosh (1965a); since then many more studies have shown the same general trend. Mandler (1968), Paul (1966), andSiegel (1967) all obtained an ORE using a large reward and all found that overtraining produced more initial errors. Eimas (1967), Mandler (1966, and Paul and Havlena (1965) all failed to find an ORE using a small reward; but again they all found that overtraining increased resistance to extinction.…”
Section: Attention and Frustration As Joint Explanations Of The Orementioning
confidence: 99%
“…These fall into two general categories called correction and noncorrection training procedures. However, even within these general categories, there have been procedural differences which lead to behavioral effects (Paul, 1966;Robbins, 1969).…”
mentioning
confidence: 98%